ANALYSIS OF MATURING AND MATURATION OF BURAHOL PURWODADI BOTANICAL GARDEN COLLECTION - Ramadhan, Riski Jefri; Nareswari, Aptika Hana Prastiwi; Hadiyanti, Nugraheni; Hapsari, Lia (Universitas Medan Area, 2025)
Fruit maturing enhances maturity and quality, making fruits more attractive. This process involves physiological and biochemical changes, including increased respiration, ethylene production, texture alteration, and heat improvement. This study examines the effects of different ethylene sources: calcium carbide (CaC2), 500 mg vitamin C, and potassium permanganate (PK), on the maturing of Burahol fruit (Stelechocarpus burahol). A Completely Randomized Factiorial Design (CRFD) with five replications was employed. Treatments included E1 (control, no ethylene), E2 (0.5% CaC2 of fruit weight wrapped in cloth), E3 (500 mg vitamin C/kg fruit), and E4 (PK crystals in a sealed chamber). Data collected on day three evaluated skin color (RHS charts), texture, and mucus presence. Results showed CaC2 and PK induced optimal maturing, yielding uniformly brownish-yellow fruits (20A/Brilliant Yellow), firm texture, and no mucus. Vitamin C fails to prevent decay due to mechanical damage from forced harvesting. This study highlights CaC2 and PK as effective maturing agents, providing practical solutions for Burahol fruit post-harvest management.